Critical appraisal of laropiprant and extended-release niacin combination in the management of mixed dyslipidemias and primary hypercholesterolemia - Ayman A Hussein; Stephen J Nicholls (Dove Medical Press, 2010)
Ayman A Hussein, Stephen J NichollsCardiovascular Medicine Department, Cleveland Clinic Foundation, Cleveland, OH, USAAbstract: Niacin is a B-complex vitamin which has been used for decades for the management of mixed dyslipidemias and primary hypercholesterolemia. It decreases the risk of cardiovascular events either when used as a monotherapy or in combination with other lipid lowering medications. However, a major limitation to its use is niacin-induced flushing occurring even with the extended-release formulations. Laropiprant, a selective prostaglandin-2 receptor inhibitor, specifically targets the cascade of events causing the flushing. It has been recently used in combination with extended-release niacin. This article will review the early experience with this combination with focus on efficacy, safety, tolerability and current place in therapy. Early data are promising and suggest that more patients in clinical practice will benefit from niacin combined with laropiprant. Ongoing clinical trials will provide a better insight on the long-term safety of the drug and its efficacy for reducing cardiovascular events.Keywords: niacin, laropiprant, dyslipidemias, hypercholesterolemia